Tales of addiction and recovery understanding the narratives of recovering addicts at the New Day Recovery Center - Cartagena, Karla Ann Katrina M.
The goal of its qualitative research was to understand how stories within a support group contribute to the development of collective consciousness. The participants of this study were the resident recovering addicts of the New Day recovery Center. Two consecutive meetings of the support group were attended by the researcher and five interviews were conducted, all these were recorded, transcribed and analyzed using Fisher?s Narrative Paradigm Theory and Bormann?s Symbolic Convergence Theory. The results reveal a prototype story which serves as a guide on how members of the support group could see their own stories. The prototype story proved to be compelling tale that influenced the members? behavior, beliefs and actions. This study showed the stories in support groups, especially in 12 step programs are key to the groups? success. Stories bind members together by helping them make sense of their own experience, exchange knowledge, forge bonds and create a shared reality. All these consequently lead to a more cohesive group